Synthesis of 2-aryl substituted 2,3-dihydroquinazoline-4(1H)-ones under solvent free conditions using ionic liquid as a mild and efficient catalyst - Obaiah, Obaiah; Kebbahalli, Nandeesh Nagalingaiah; Goravanahalli, Raghavendra Manchigaiah; Chottanahalli, Pavankumar Siddalingaiah; Kanchugarakoppal, Rangappa Subbegowda; Kempegowda, Mantelingu (European Journal of Chemistry, 2014)
A simple, green and environmentally benign procedure has been developed for the synthesis of 2,3-dihydroquinazoline-4(1H)-ones in basic ionic liquid via the cyclocondensation of 2-amino benzamide with an aldehyde. This offers several advantages such as high yields, simple procedure, low cost, short reaction times, mild and solvent free condition.